2018
DOI: 10.1001/jamaophthalmol.2018.1934
|View full text |Cite
|
Sign up to set email alerts
|

Automated Diagnosis of Plus Disease in Retinopathy of Prematurity Using Deep Convolutional Neural Networks

Abstract: ; for the Imaging and Informatics in Retinopathy of Prematurity (i-ROP) Research Consortium IMPORTANCE Retinopathy of prematurity (ROP) is a leading cause of childhood blindness worldwide. The decision to treat is primarily based on the presence of plus disease, defined as dilation and tortuosity of retinal vessels. However, clinical diagnosis of plus disease is highly subjective and variable. OBJECTIVE To implement and validate an algorithm based on deep learning to automatically diagnose plus disease from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
341
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 515 publications
(376 citation statements)
references
References 45 publications
5
341
0
2
Order By: Relevance
“…We have previously shown that this system has very high accuracy for plus disease in ROP 15. These results extend those findings beyond plus disease and demonstrate that despite only being trained to recognise plus disease, the system has high accuracy for broader diagnostic categories of ROP, particularly severe disease.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…We have previously shown that this system has very high accuracy for plus disease in ROP 15. These results extend those findings beyond plus disease and demonstrate that despite only being trained to recognise plus disease, the system has high accuracy for broader diagnostic categories of ROP, particularly severe disease.…”
Section: Discussionsupporting
confidence: 79%
“…The i-ROP DL system was developed based on the concept of convolutional neural networks using methods previously published 15. Briefly, a reference standard diagnosis of plus disease was established by analysing 5511 wide-angle image sets from ROP screening in at-risk neonates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations